Real leaders don't do PowerPoint : how to sell yourself and your ideas. - Witt, Christopher, ....- (New York : Crown Business, 2009)
Think about the most powerful speech you've ever heard a leader give. What made that speech-and that speaker-memorable was likely a mix of authenticity, stage presence, masterful delivery, and-above all-an inspirational message. Nobody ever walked out of a great speech saying, 'I loved the way she used PowerPoint.' Yet, all too often, speakers rely on tools like it to carry them through a presentation. Real leaders speak to make a difference, to promote a vision, to change the way people think and feel and act. Their ability to lead goes hand in hand with their ability to get their message across, no matter what size audience they're addressing. Drawing on his years of experience in coaching executives, Christopher Witt shows not just how to make a speech but why and when you should make one. His practical advice on how to take your game to the next level includes: Â You are the message. Who you are-your character, experience, values-shapes the message your listeners hear. Â Content is king. Delivery is important, but it is only the helpful-or unhelpful-servant of your message. So build each speech around one, and only one, 'Big Idea.' Â A confused mind always says no. When you want your listeners to say yes, you've got to make them understand what you want them to do and why they should care. Â Dare to do the unexpected. Leaders know the rules, and they know when, why, and how to break them. In chapters that can be read in five minutes or less and in a book that can be gone through in one sitting, Witt shows you how to become more confident, more commanding, more compelling speakers. But this isn't just a book about speaking. It's about leadership and about how people-CEOs and PTA presidents, small business owners and sales reps, middle managers and techno geeks-can present themselves and their ideas with greater impact.
Keywords: Communicatie ; mondeling; Spreken